Dice World: Science and Life in a Random Universe - Brian Clegg (Icon, 2013)
As troubling as we pattern-seeking humans may find it, modern science has repeatedly shown us that randomness is the underlying heartbeat of nature. In Dice World, acclaimed science writer Brian Clegg takes readers on an incredible trip around our random universe, uncovering the truths and lies behind probability and statistics, explaining how chaotic intervention is behind every great success in business, and demonstrating the possibilities quantum mechanics has given us for creating unbreakable ciphers and undergoing teleportation. He explores how the 'clockwork universe' imagined by Newton, in which everything could be predicted given enough data, was disproved bit by bit, to be supplanted by chaos theory and quantum physics. Clegg reveals a world in which not only is accurate forecasting often impossible but probability is the only way for us to understand the fundamental nature of things. Forget the clockwork universe. Welcome to Dice World, a unique portrait of a startlingly complex cosmos, from the bizarre microscopic world of the quantum to the unfathomable mechanics of planetary movements, where very little is as it seems